2014
DOI: 10.1158/1078-0432.ccr-14-0257
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of Muscle-Invasive Bladder Cancer Identifies Recurrent Mutations of UNC5C and Prognostic Importance of DNA Repair Gene Mutations on Survival

Abstract: Purpose Due to suboptimal outcomes in muscle-invasive bladder cancer even with multimodality therapy, determination of potential genetic drivers offers the possibility of improving therapeutic approaches and discovering novel prognostic indicators. Experimental Design Using pTN staging, we case-matched 81 patients with resected ≥pT2 bladder cancers for whom perioperative chemotherapy use and disease recurrence status were known. Whole exome sequencing was conducted in 43 cases to identify recurrent somatic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…Eleven genes encoding proteins involved in phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-mammalian target of rapamycin (mTOR) signaling were altered in 60% of the lines, most frequently by altered PI3K regulatory subunit (PIK3CA) and the tyrosine kinase gene, ERBB2 . In agreement with previous observations (2,28), the BRCA DNA repair pathway, including BRCA1 and ATM , were altered in 44% of lines in a predominantly mutually exclusive manner. This is similar to 40/127 (32%) of tumors from TCGA patients (4) which also exhibited BRCA pathway gene alterations that were predominantly mutually exclusive.…”
Section: Resultssupporting
confidence: 93%
“…Eleven genes encoding proteins involved in phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-mammalian target of rapamycin (mTOR) signaling were altered in 60% of the lines, most frequently by altered PI3K regulatory subunit (PIK3CA) and the tyrosine kinase gene, ERBB2 . In agreement with previous observations (2,28), the BRCA DNA repair pathway, including BRCA1 and ATM , were altered in 44% of lines in a predominantly mutually exclusive manner. This is similar to 40/127 (32%) of tumors from TCGA patients (4) which also exhibited BRCA pathway gene alterations that were predominantly mutually exclusive.…”
Section: Resultssupporting
confidence: 93%
“…Tumors with mutation in at least one of these genes had significantly higher overall numbers of somatic mutations 25 and longer recurrence-free survival. Similarly, we observed that number of alterations in DDR genes was positively correlated with total number of mutations and copy number alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods less frequently usednot measured in our study include the Maxwell 16 method by Promega (Mannheim, Germany), which was shown to perform well against other automated Qiagen kits [9], and the Chelex bead method (Bio-Rad, Berkeley, California) which has been used with some success in manual or automated extractions from FFPE tissues [10]. A small number of studies have shown that the DNA obtained by a recent sonication-based method called adaptive focused acoustics (AFA) is more amenable to next generation sequencing than DNA from other methods, resulting in greater coverage of the genome and facilitating easier assembly and alignment [11][12][13]. To our knowledge, ours is the first study to compare AFA for use in aCGH.…”
Section: Introductionmentioning
confidence: 99%